Bioarchaeological study of ancient Teotihuacans based on complete mitochondrial genome sequences and diet isotopes - Fuzuki Mizuno; Fuyuki Tokanai; Masahiko Kumagai; Koji Ishiya; Saburo Sugiyama; Michiko Hayashi; Kunihiko Kurosaki; Shintaroh Ueda (Taylor & Francis Group, 2023)
Background The Teotihuacan civilisation was the largest one in ancient Mesoamerica. The Teotihuacan city was born in the north-eastern Basin of Mexico around the second century BC, reached its peak in the fourth century AD, and had cultural influence throughout Mesoamerica. At its peak, the size of the city reached more than 20 km2, and the total population is estimated to have increased from 100,000 to 200,000. However, knowledge of the genetic background of the Teotihuacan people is still limited. Aim We aimed to determine the mitogenome sequences of the Teotihuacan human remains and compare the ancient and present Mesoamericans. In addition, we aimed to identify the food habits of ancient Teotihuacans. Subjects and methods We determined the mitogenome sequences of human remains dated to 250-636 cal AD using target enrichment-coupled next generation sequencing. We also performed stable isotope analysis. Results We successfully obtained nearly full-length sequences newly unearthed from a civilian dwelling in the Teotihuacan site. Teotihuacan mitochondrial DNA was classified into the haplogroups in present and ancient Mesoamericans. In addition, Teotihuacan individuals had a diet dependent on C4 plants such as maize. Conclusion Genetic diversity varied among the Teotihuacans.